Control interno contable de los inventarios y su aporte a la razonabilidad de los estados financieros - Cuchimbo Laines, Yulisa Priscila (2015)
The integration project is aimed to give a real insight into one of the problems that mostly indexed on the competitiveness of companies engaged in the commercialization of fuel, the primary objective the development and implementation of a guidance document structured around functions processes and accounting nature. the integration project started with bases in the careful selection of scientific articles ( papers) which is directly the problem under study and later make a field investigation focused on dialogue and analysis to staff working in the Gasolinera del Sindicato de Choferes Profesionales del Guabo and where the absence of a control fuel inventory is determined, the same that is impacting the business of the company, should also be mentioned that due to the lack of a guidance document the authorities know the exact volume inventory they have and the amount that represents this. It is important to emphasize that the proposal was referred to previously submitted to the relevant authorities for analysis and approval and the related statement the same guidance document which provides key findings and recommendations for implementation.